Source-Sink Manipulation and Its Impacts on Canola Seed Filling Period - D. Ricciuto; M. A. Secchi; A. J. P. Carcedo; L. Nieto; J. Lacasa; M. Stamm; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2023)
Canola yield production is driven by the balance between source (leaves) and sink (pods and seeds) activity during the reproductive period of a crop. However, previous literature has not reported the impact of source-sink limitations under different nitrogen (N) supplies, and its effect on seed filling. Therefore, the objectives of this study were to 1) explore the impact of source-sink manipulations during the seed filling period and its main parameters: duration and rate; and 2) understand the interactions between N supply and source-sink manipulations to explain variations in seed weight. With these objectives, a field experiment was conducted during 2019–2020 and 2020–2021 (Kansas, U.S.). One winter canola hybrid was tested under two N fertilization levels (0 and 134 lb/a), and three source-sink modifications (control; reduced sink, 50% pod removal at pod setting; and reduced source, 100% defoliation at pod setting). The reduced sink treatment resulted in a larger seed weight relative to the control. The duration of seed filling was longer for the control relative to the rest of the treatments. Even though no significant differences were found with different N fertilization, the highest seed weight values were obtained with the high N level (134 lb/a).
Keywords: nitrogen supply; seed filling duration; seed filling rate; Brassica napus L.